2017
DOI: 10.1002/biot.201700496
|View full text |Cite
|
Sign up to set email alerts
|

Alga‐Made Anti‐Hepatitis B Antibody Binds to Human Fcγ Receptors

Abstract: Microalgae are unicellular eukaryotic organisms which represent an emerging alternative to other cell biofactories commonly used to produce monoclonal antibodies. Microalgae display several biotechnological advantages such as their rapid growth rate and their phototrophic lifestyle allowing low production costs as protein expression is solar-fueled. Recently, a fully assembled recombinant IgG antibody directed against Hepatitis B surface antigen is produced and secreted in the culture medium of the diatom Phae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 72 publications
(127 reference statements)
0
23
0
Order By: Relevance
“…In addition, the mAb directed against the Hepatitis B was demonstrated to be of good quality, homogenous and glycosylated with oligomannosides (Vanier et al, 2015). This mAb is also able to bind to human Fcγ receptors (FcγRI and FcγRIIIa in particular) which suggests that it could be efficiently used in human immunotherapy to induce phagocytosis and antibody dependent cell-mediated cytotoxicity response (Vanier et al, 2018). Such therapeutic application represents currently a multimillion dollar market sales (Walsh, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the mAb directed against the Hepatitis B was demonstrated to be of good quality, homogenous and glycosylated with oligomannosides (Vanier et al, 2015). This mAb is also able to bind to human Fcγ receptors (FcγRI and FcγRIIIa in particular) which suggests that it could be efficiently used in human immunotherapy to induce phagocytosis and antibody dependent cell-mediated cytotoxicity response (Vanier et al, 2018). Such therapeutic application represents currently a multimillion dollar market sales (Walsh, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…However, when compared to a human IgG1 used as a control, affinity of the diatom-made mAb is 4.5-fold lower than the one of the human IgG1 for FcγRI and three-times higher for FcγRIIIa. Such differences in kinetics and affinity are due to N -glycosylation variance (Vanier et al, 2018). Therefore, it would be necessary in the future to engineer the N -glycosylation of diatom-produced mAb to favor the presence of complex-type and fine-tuned N -glycans as it is well established that glycosylation of mAbs and biopharmaceuticals in general influences their biological functionality and efficacy (Lingg et al, 2012; Buettner et al, 2018; Mimura et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the efficient production of these antibodies in diatoms couldn't be without the implication of PTMs of P. tricornutum which was mainly the glycosylation. Interestingly, analyzes with the Western Blot technique proved that P. tricornutum has established glycosylation in its endoplasmic reticulum for the chains of the antibody protein surface produced [100]. The diversified PTMs in diatoms represent an additional feature encouraging using these creatures to become complex protein production platforms compared to bacteria and yeast that shows a relative lack of PTMs.…”
Section: Translational Modifications Post-translational Modificationmentioning
confidence: 99%
“…The latter has been biochemically characterized in order to check the quality of the diatom-made mAb as well as its N-glycosylation profile [15]. Moreover, it has been demonstrated that this glycosylated antibody is able to bind human Fcy receptors [16], thus suggesting that it could be efficient in human therapy.…”
Section: Introductionmentioning
confidence: 99%